2016
DOI: 10.4049/jimmunol.1600879
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Epitopes That Expand High-Avidity CD4+ T Cells Transforms Subprotective Vaccines to Efficacious Immunogens against Virulent Francisella tularensis

Abstract: T cells are the immunological cornerstone in host defense against infections by intracellular bacterial pathogens, such as virulent Francisella tularensis (Ftt). The general paucity of novel vaccines for Ftt over the past 60 years can, in part, be attributed to the poor understanding of immune parameters required to survive infection. Thus, we developed a strategy utilizing classical immunological tools to elucidate requirements for effective adaptive immune responses directed against Ftt. Following generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 39 publications
0
32
0
1
Order By: Relevance
“…Animal studies have previously shown that B and T cell responses are important in the induction and regulation of an effective immune response to live tularemia vaccines [5,6]; specifically, maintaining either CD4+ or CD8+ T cells in mice appeared to be essential for survival. Animals challenged with virulent Francisella require both T cell subsets for survival [7,8], and in vitro studies of human cells suggest that CD8+ T cell proliferation and cell survival depend on CD4+ proliferation [9]. However, the natural course and efficacy of acquired immunity is not well studied in large human cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have previously shown that B and T cell responses are important in the induction and regulation of an effective immune response to live tularemia vaccines [5,6]; specifically, maintaining either CD4+ or CD8+ T cells in mice appeared to be essential for survival. Animals challenged with virulent Francisella require both T cell subsets for survival [7,8], and in vitro studies of human cells suggest that CD8+ T cell proliferation and cell survival depend on CD4+ proliferation [9]. However, the natural course and efficacy of acquired immunity is not well studied in large human cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…To inform our antigen down selection process, we attempted to assess the in vitro antimicrobial potential of vaccine induced immunity using a functional killing assay based on previously reported methodology [ 35 ]. Splenocytes from immunized mice were stimulated overnight with heat-killed F .…”
Section: Resultsmentioning
confidence: 99%
“…The macrophage/splenocyte co-culture killing assay was a modification of a method from Roberts et al [ 35 ]. In summary, murine splenocytes were isolated as described above and cultured in L15 medium (Life Sciences, UK) with either medium alone, 10 ng/ml phorbol myristate acetate(PMA; Sigma) + 1ug/ml ionomycin (Sigma) or heat killed F .…”
Section: Methodsmentioning
confidence: 99%
“…Antibody-mediated immunity appears to be a poor correlate of immunity to highly virulent F. tularensis strains; antibody titers do not correlate with protection in humans[15], and the transfer of immune serum fails to protect recipient mice against the challenge with virulent strain of F. tularensis [1618]. In contrast, both CD4 + and CD8 + T cells are known to be required for protection, as depletion of either subset abolishes protective immunity [12,19,20]. To truly hone in on correlates of protective T cell responses, it is necessary to be able to differentiate cells specifically responding to the pathogen of interest from cells of other specificities [21].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a protective vaccine leads to more antigen-specific CD4 + T EM in the mediastinal lymph node (MLN) and spleen, as compared to a non-protective vaccine [20]. Additionally, the tool has been used to study how these cells respond to a prime-boost strategy [13] and has revealed the dramatic influence high avidity CD4 + T cell epitopes have on protection [13,20]. While this tool will undoubtedly yield many more insights into the role of CD4 + T cells in immunity to F. tularensis, no such tool currently exists to characterize CD8 + T cells, which are also required for protection against this predominantly intracellular pathogen [12,19,20].…”
Section: Introductionmentioning
confidence: 99%